Cloning and sequence analysis of cDNA encoding urotensin I precursor. - Ishida, I (1986)
The primary structure of the precursor of urotensin I, a neuropeptide hormone from the caudal neurosecretory system of the carp Cyprinus carpio, has been determined by analyzing the nucleotide sequence of cloned DNA complementary to the mRNA encoding it. The precursor consists of 145 amino acid residues and the carboxyl terminus represents the 41-amino acid sequence of urotensin I, preceded by Lys-Arg and followed by Gly-Lys. Sequence homology as well as similar organization of the precursors of urotensin I and mammalian corticotropin-releasing factors suggest that they are evolutionarily related. RNA transfer blot analysis indicates that mRNA encoding the precursor of urotensin I is present only in the spinal cord and not in the brain, intestine, liver, or kidney of the carp.